ANALISIS KEMAMPUAN MENYELESAIKAN SOAL HOTS FISIKA MATERI GETARAN HARMONIS DI SMA KRISTEN IMMANUEL PONTIANAK - Ariansyah, Ariansyah; Sahala S, Stepanus; Arsyid, Syaiful B (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to analyze students ability to solve Higher Order Thinking Skills (HOTS) problems in physics, especially in simple harmonic motion in SMA Kristen Immanuel Pontianak. The methods used in this research was descriptive method with qualitative approach. The subjects in this research is 60 students of class XI MIPA. The data-collecting instruments in this research was ten essay problems, consists of analyze, evaluate, and create step of thinking. According to the data result of this research, it is concluded that the students ability to analyze problems 43,13%, while the average of stdents evaluate ability are 41% and students create ability are 12.67%. The result of mann-whitney were asymp. Sig. (2-tailed) score of 0,075 (>0,05), so H0 are accepted and H1 are denied. It means that there aren't significant difference between the average of the result of students problem solving abilities of male and female students. Those results show that students abilities of solving high order thinking problems still categorised as low. Therefore, the remediation of learning activities in class still needed in order to increase students high order thinking skill in SMA Kristen Immanuel Pontianak. Keyword: Analysis, Higher Order Thinking Skills, Simple harmonic motion